Multi-layer co-extrusion optical thin film and preparation method thereof
Through multi-layer co-extruded optical film technology, multiple functional layers are integrated in the one-time molding process, solving the problems of process complexity and performance in the existing technology, and achieving efficient, economical and stable film production and performance improvements .
Patent Information
- Application Number
- CN202411598709.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
The existing multi-layer optical film technology faces problems such as process complexity, poor interlayer adhesion, mismatch of material performance and difficulty in functional integration, resulting in complex production, high cost and unstable performance.
Using multi-layer co-extruded optical film technology, multiple functional layers are integrated into the same film through a one-time molding process, including polymer substrate layer, ultraviolet barrier film, multi-layer reflective film, thermal reflective film, superhydrophobic coating and The anti-scratch protective layer is uniformly distributed and closely combined with the layers using melt coextrusion technology and sol-gel method.
It realizes efficient, economical and stable production of films, improves the optical performance, thermal management performance, protection performance and cleanliness of films, simplifies production processes and improves performance consistency and stability.
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a multi-layer co-extruded optical film and a preparation method thereof. Background Art
[0002] With the development of modern science and technology, especially in the fields of display technology, automotive glass, building materials, electronic products, etc., the performance requirements for film materials are increasing. In order to meet these needs, optical film technology continues to develop in the direction of multifunctional integration, improved durability and processing efficiency. In recent years, the research and application of optical films have made significant progress in various industries, especially multi-layer co-extruded optical films as a new material system, with its good functional integration, processing efficiency and excellent physical properties, it has become one of the key materials in many industries.
[0003] In traditional film materials, different functions are usually handled separately. For example, UV blocking, reflection, scratch resistance and other properties often rely on different single-layer films or coatings, which not only increases the complexity of production, but also leads to coupling problems between different functions. The performance of each layer of film may be affected by other layers, and the bonding strength and durability of multi-layer films have also become technical challenges.
[0004] In order to solve this problem, multilayer optical films based on co-extrusion technology have been proposed and widely used in recent years. Co-extrusion technology processes multiple functional layers simultaneously in a single molding process, so that different functional layers can be evenly distributed and tightly combined in the film, which not only simplifies the manufacturing process, but also improves the performance stability and consistency of the film material. Through reasonable multi-layer structure design, this film can simultaneously achieve multiple functions, such as optical protection, thermal management, anti-fouling and waterproofing, etc.
[0005] Although the existing multilayer optical film technology has made certain application progress in various fields, it still faces some challenges and problems:
[0006] Process complexity: Traditional multi-layer film production methods, such as lamination and coating, often require multiple processing steps, and the manufacture of each layer of film may require different process conditions, which increases the complexity and cost of production.
[0007] Poor interlayer adhesion: The combination of different materials may cause interlayer separation and falling off, affecting the overall stability and performance consistency of the film.
[0008] Mismatched material properties: The combination of multiple materials may lead to differences in their thermal expansion coefficients, surface energy, mechanical strength, etc., thus affecting the long-term stability of the film.
[0009] Functional integration is difficult: Integrating multiple functions (such as UV blocking, reflection, scratch resistance, anti-fouling, etc.) into the same film requires precise design of the performance and thickness of each layer of the film to ensure synergy between different functions, and this process is often complicated in traditional multi-layer film production. Summary of the invention
[0010] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide a multi-layer co-extruded optical film and a method for preparing the same. The multi-layer co-extruded optical film can simultaneously integrate multiple functional layers into the same film through a one-time molding process, effectively overcoming some technical difficulties in the traditional film production process and providing a more efficient, economical and stable solution.
[0011] The primary purpose of the present invention is achieved through the following technical solutions:
[0012] A multi-layer co-extruded optical film, the film is composed of the following components:
[0013] a polymer substrate layer, the layer consisting of polyester and polymethyl methacrylate;
[0014] UV blocking film, which is composed of titanium dioxide and zinc dioxide;
[0015] Multilayer reflective film, which is formed by alternating stacking of high refractive index materials and low refractive index materials;
[0016] Heat reflective film, which is composed of metallic reflective material;
[0017] a superhydrophobic coating composed of a fluorinated polymer;
[0018] Anti-scratch protective layer, the protective layer consists of polyurethane material.
[0019] Preferably, the polymer substrate layer consists of a mixture of polyethylene terephthalate and polymethyl methacrylate.
[0020] Preferably, the ultraviolet blocking film is formed by a sol-gel method, and the titanium dioxide and zinc dioxide are dispersed in a transparent substrate in the form of nanoparticles.
[0021] Preferably, the multilayer reflective film is composed of at least 10 layers of alternatingly stacked high-refractive-index materials and low-refractive-index materials.
[0022] Preferably, the super hydrophobic coating is made of fluorinated vinyl or fluorinated polyurethane material.
[0023] Preferably, the anti-scratch protective layer is a polyurethane coating with a hardness greater than 4H and a coating thickness of 0.5-2.0 μm.
[0024] Preferably, the thickness ratio of the polymer substrate layer, the UV blocking film and the multilayer reflective film is 1:1:2.
[0025] Preferably, the high refractive index material is one of titanium dioxide, silicon dioxide and zinc sulfide, the low refractive index material is one of silicon dioxide and magnesium fluoride, and the metal reflective material is one of aluminum, silver or nickel.
[0026] Preferably, the film is formed by co-extrusion, and all layer materials are co-extruded simultaneously through multiple extruders in a molten state, and the total thickness of the film is between 10 μm and 100 μm.
[0027] Another technical problem to be solved by the present invention is to provide a method for preparing a multi-layer co-extruded optical film, comprising the following steps:
[0028] The polyester and polymethyl methacrylate are mixed in a certain proportion, an appropriate amount of additives are added, and then a uniform polymer substrate layer is formed by melt co-extrusion technology;
[0029] The titanium dioxide and zinc dioxide powders are dispersed in a suitable solvent, the titanium dioxide and zinc dioxide are mixed by a sol-gel method, and then coated on the surface of the polymer substrate layer, and then heat-treated to remove the solvent to form a UV blocking film;
[0030] Using alternating evaporation deposition technology, high refractive index material and low refractive index material are deposited layer by layer on the UV blocking film. The thickness of each layer of material is usually 20-30nm to form the required multi-layer reflective film.
[0031] Using physical vapor deposition method, metal reflective material is evaporated on the top layer of multi-layer reflective film;
[0032] The fluorinated polymer is coated on the heat reflective film, and the fluorinated polymer is evenly coated on the surface of the film by a solution coating method, and then dried after coating;
[0033] Applying polyurethane material as an anti-scratch protective layer, the protective layer is applied by solution coating, and heat curing is performed after the coating is completed;
[0034] After the above steps are completed, all layers of the film are subjected to an overall heat pressing treatment at a temperature of 100-150°C for 15-30 minutes.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] This solution can effectively improve the optical performance of the film by designing multiple layers with different functions in the film, combining UV blocking film, multilayer reflective film, heat reflective film, etc. The combination of these layers can achieve: UV blocking film can effectively block the transmission of UV rays through the action of titanium dioxide and zinc dioxide, protecting the underlying materials or products from UV damage; the alternating stacking structure of multilayer reflective film (alternating high refractive index and low refractive index materials) can achieve excellent reflection effect, improve the film's reflection or transmission control of light within a specific spectral range, thereby optimizing the film's optical properties and enhancing its performance in specific applications (such as display screens, optical filters, etc.); heat reflective film effectively blocks thermal radiation through metal reflective materials (such as aluminum, silver, etc.), thereby optimizing the film's thermal management performance, reducing heat accumulation, and avoiding damage or performance degradation of the film due to overheating.
[0037] The anti-scratch protective layer (composed of polyurethane material) can provide additional mechanical strength for the film, prevent surface scratches and damage, and extend the service life of the film; the super-hydrophobic coating can give the film super-hydrophobicity through the addition of fluorinated polymers, so that its surface has excellent water droplet repellency, reduces water stain accumulation and stain adhesion, and improves the cleanliness and maintainability of the film.
[0038] Through multi-layer co-extrusion technology, multiple layers with different functions can be prepared and superimposed at one time in the same production process, simplifying the production process and improving production efficiency. Compared with traditional lamination or coating technology, this method has higher production efficiency and cost-effectiveness; multi-layer co-extrusion can ensure the uniformity and close combination of each functional layer, avoid separation or gaps between layers, and help improve the overall stability and performance consistency of the film.
[0039] This technical solution can integrate multiple functions such as optical performance, thermal management, protective performance and cleanability into the same film, meeting the needs of modern electronic products, automotive glass, architectural window films and other fields for multifunctional films. For example, on automotive glass or architectural glass, in addition to providing optical protection and thermal isolation, it also requires good scratch resistance and anti-fouling properties to prevent the glass surface from being affected by water stains, dirt or scratches, which may affect its appearance and service life. DETAILED DESCRIPTION
[0040] The specific implementation modes of the present invention are further described in detail to make the technical solutions of the present invention easier to understand and grasp.
[0041] Example 1
[0042] A method for preparing a multi-layer co-extruded optical film comprises the following steps:
[0043] Preparation of polymer substrate layer
[0044] Material selection: A mixture of polyester (PET) and polymethyl methacrylate (PMMA) is used as the raw material for the substrate layer, and the specific proportions are:
[0045] Polyester (PET): 70%
[0046] Polymethyl methacrylate (PMMA): 30%
[0047] Additives: 1% stabilizer (antioxidant), 1% plasticizer, and 0.5% UV inhibitor were added to improve the thermal stability and UV resistance of the material.
[0048] Molding process: Molding is carried out by melt co-extrusion technology. The molding temperature range is 240℃ to 270℃, and the thickness of the substrate layer is controlled between 1 and 10μm.
[0049] The end result: a transparent polymer substrate layer with good mechanical properties.
[0050] Preparation of UV-blocking film
[0051] Material selection: The UV blocking film is a mixture of titanium dioxide (TiO2) and zinc dioxide (ZnO), and the specific composition ratio is:
[0052] Titanium dioxide (TiO2): 75%
[0053] Zinc dioxide (ZnO): 25%
[0054] Solution preparation: Using isopropyl alcohol (IPA) as a solvent, the solid particle concentration of TiO2 and ZnO is adjusted to 10%-20%, and the ultraviolet blocking film solution is prepared by a sol-gel method.
[0055] Coating process: Spin-coat the prepared solution onto the surface of the polymer substrate layer, and the coating thickness is controlled at 0.5 to 2.0 μm.
[0056] Heat treatment: The coated substrate layer is treated by a heat treatment process at a temperature of 150°C to 180°C for 30 to 60 minutes to promote the adhesion and curing of the UV blocking film.
[0057] Preparation of multilayer reflective films
[0058] Material selection: The multilayer reflective film is made by alternating high refractive index materials and low refractive index materials. The specific materials and thicknesses are as follows:
[0059] High refractive index material (TiO2): 20-30nm / layer;
[0060] Low refractive index material (SiO2): 20-30nm / layer;
[0061] Stacking structure: High refractive index materials and low refractive index materials are stacked alternately, with a total of 10 layers stacked to form a reflective film. The thickness of each layer is controlled between 20 and 30nm.
[0062] Deposition process: Physical vapor deposition (PVD) technology is used to deposit the reflective film, and the deposition temperature is controlled at 100°C to 150°C.
[0063] The final effect: a multilayer reflective film with high reflectivity (>90% in the 800-1000nm band) is formed.
[0064] Preparation of heat reflective film
[0065] Material selection: The heat reflective film uses aluminum (Al) as the metal reflective material, and the thickness of the aluminum is controlled between 100 and 200 nm.
[0066] Deposition process: Physical vapor deposition (PVD) technology is used to deposit aluminum film to ensure uniform film layer and good adhesion.
[0067] Final effect: Aluminum reflective film provides good heat reflection performance and effectively reduces heat radiation conduction.
[0068] Preparation of superhydrophobic coating
[0069] Material selection: Fluorinated polymer (PVDF or FPU) is used as the material of the super-hydrophobic coating, and the coating thickness is controlled between 50 and 200 nm.
[0070] Coating process: The fluorinated polymer is coated on the surface of the membrane by solution coating, and the solid content of the coating liquid is 5%-10%.
[0071] Drying treatment: The coated film is dried at a temperature of 80°C to 120°C for 10 to 20 minutes.
[0072] The final effect: The coating surface has a water contact angle of more than 150°, showing excellent superhydrophobicity.
[0073] Preparation of anti-scratch protective layer
[0074] Material selection: The anti-scratch protective layer is made of polyurethane (PU) with a hardness of more than 4H.
[0075] Coating process: The polyurethane protective layer is coated by solution coating, and the solid content of the coating liquid is 15%-25%.
[0076] Thermal curing treatment: The coated film is thermally cured at a temperature of 140°C to 160°C for 30 to 60 minutes.
[0077] Final effect: The anti-scratch protective layer gives the film stronger surface wear resistance and reduces scratch damage.
[0078] Heat pressing
[0079] Hot pressing process: All layers are combined by hot pressing process. The hot pressing temperature is 100℃ to 150℃, the pressure is moderate, and the time is 15 to 30 minutes.
[0080] Cooling process: Use natural cooling or air cooling to ensure that the film layer is evenly bonded and free of bubbles.
[0081] Final product performance testing
[0082] UV blocking performance: Tested with UV-Vis spectrometer to ensure UV transmittance ≤1%.
[0083] Heat reflective performance: Reflectivity tests show that the reflectivity in the 800-1000nm band reaches over 90%.
[0084] Scratch resistance: Through the pencil hardness test, the coating hardness reaches 4H, ensuring that the film layer has good scratch resistance.
[0085] Super hydrophobic performance: The water contact angle test shows that the water contact angle on the coating surface is greater than 150°, showing extremely strong super hydrophobic performance.
[0086] Optical transparency: The transmittance test shows that the transmittance of the film is greater than 80%, ensuring the high transparency of the film.
[0087] Example 2
[0088] A method for preparing a multi-layer co-extruded optical film comprises the following steps:
[0089] Preparation of substrate layer
[0090] Material selection: A mixture of polypropylene (PP) and polyvinyl chloride (PVC) is selected as the base material layer, the proportion is:
[0091] Polypropylene (PP): 60%
[0092] Polyvinyl chloride (PVC): 40%
[0093] Additives: 2% UV stabilizer (UV-622), 3% plasticizer, and 1.5% antibacterial agent (silver ion complex) were added.
[0094] Molding process: Co-extrusion molding technology is adopted, the thickness of the substrate layer is controlled between 5 and 15 μm, and the extrusion temperature is set at 220℃ to 250℃.
[0095] The final effect: a transparent substrate layer with good weather resistance and toughness is obtained.
[0096] Preparation of UV blocking layer
[0097] Material selection: The UV blocking layer is made of a composite material of aluminum oxide (Al2O3) and titanium oxide (TiO2), and the specific composition ratio is:
[0098] Alumina (Al2O3): 60%
[0099] Titanium oxide (TiO2): 40%
[0100] Solution preparation: Al2O3 and TiO2 powders were mixed with deionized water and ethanol by the sol-gel method to form a solution with a concentration of 8%-12%.
[0101] Coating process: The UV blocking layer is evenly coated on the surface of the substrate by spin coating, and the coating thickness is controlled at 0.5 to 1.5 μm.
[0102] Heat treatment: The coated film is baked at 130℃ to 160℃ for 20 to 30 minutes to ensure the crystallization and adhesion of the UV blocking layer.
[0103] Preparation of thermal isolation film
[0104] Material selection: The thermal isolation membrane is made of a composite material of graphene and polytetrafluoroethylene (PTFE), with a graphene content of 20%-30%.
[0105] Solution preparation: Graphene and PTFE are combined by solution polymerization to prepare a 10%-15% composite solution.
[0106] Coating process: The composite solution is coated on the substrate layer by dip coating to ensure uniform coating and control the thickness between 1 and 3 μm.
[0107] Curing treatment: Use hot pressing curing method with the temperature set at 160°C to 180°C for 10 to 20 minutes to ensure full bonding of graphene and PTFE.
[0108] Preparation of antifouling self-cleaning coating
[0109] Material selection: The anti-fouling self-cleaning coating is made of a composite material of silicon dioxide (SiO2) and fluorinated polymer. The specific ratio is:
[0110] Silicon dioxide (SiO2): 70%
[0111] Fluorinated polymer (PTFE): 30%
[0112] Solution preparation: Silicon dioxide and fluorinated polymer are dissolved in an alcohol solvent by a sol-gel method to form a 5%-10% coating solution.
[0113] Coating process: The coating solution is evenly applied to the membrane surface by blade coating, ensuring that the coating thickness is 0.5 to 1.0 μm.
[0114] Heat treatment: The coated film is heat treated at 140°C to 160°C for 30 minutes to ensure the durability and adhesion of the antifouling coating.
[0115] Preparation of antibacterial layer
[0116] Material selection: The antibacterial layer adopts a composite material containing silver nanoparticles, and the content of silver nanoparticles is 2%-5%.
[0117] Solution preparation: Silver nanoparticles are mixed with polymer resin (acrylic resin) to prepare a solution with a concentration of 2%-5%.
[0118] Coating process: Use the spraying method to evenly spray the antibacterial solution on the membrane surface, and the coating thickness is controlled between 0.3 and 0.5 μm.
[0119] Curing: UV curing technology is used to cure the antibacterial coating through a UV light source to ensure that the silver nanoparticles are fully distributed and not damaged.
[0120] Heat pressing
[0121] Hot pressing process: All film layers are combined by hot pressing molding process, the hot pressing temperature is set at 120℃ to 150℃, the pressure is 10 to 15MPa, and the time is controlled at 15 to 25 minutes.
[0122] Cooling process: Natural cooling to room temperature to ensure that each layer has a stable structure and uniform thickness.
[0123] Final product performance testing
[0124] UV blocking performance: Use a UV spectrometer to test the UV transmittance of the film to ensure that the UV transmittance is less than 0.5%.
[0125] Thermal insulation performance: A heat flow meter is used to test the thermal insulation performance of the membrane to ensure that the thermal resistance value reaches 0.25m 2 ·K / W or above.
[0126] Antifouling and self-cleaning properties: The water contact angle test results show that the contact angle of the membrane surface is greater than 120°, showing excellent antifouling and self-cleaning properties.
[0127] Antibacterial performance: Through the antibacterial test (standard ISO 22196 test), the membrane surface has a significant inhibitory effect on common pathogens such as Escherichia coli and Staphylococcus aureus within 24 hours, and the antibacterial rate is greater than 99%.
[0128] Optical transparency: The transmittance test results show that the transmittance of the film is higher than 85%, ensuring high light transmission performance.
[0129] Example 3
[0130] The multilayer co-extruded optical film of this embodiment includes the following components in parts by weight:
[0131] Preparation of substrate layer
[0132] Material selection: The base material layer is made of a composite material of polyester (PET) and polyurethane (PU), the specific proportions are:
[0133] Polyester (PET): 70%
[0134] Polyurethane (PU): 30%
[0135] Additives: 2% of UV stabilizer (UV-300), 1.5% of wear-resistant agent (polytetrafluoroethylene particles) and 1% of antibacterial agent (zinc ion complex) are added to polyurethane.
[0136] Molding process: The solution impregnation method is used to immerse the PET substrate in the PU solution. The solution concentration is controlled at 20%-25%. The PU material and the PET substrate layer are fully combined through heat treatment.
[0137] Final effect: A substrate layer with a thickness of about 20 μm is obtained, which has a smooth and uniform surface and high strength and toughness.
[0138] Preparation of waterproof coating
[0139] Material selection: The waterproof coating is made of a composite material of polytetrafluoroethylene (PTFE) and fluorinated polymer, with the following ratios:
[0140] Polytetrafluoroethylene (PTFE): 80%
[0141] Fluorinated polymer (fluorinated ethylene / propylene copolymer): 20%
[0142] Solution preparation: PTFE and FEP materials were mixed with an organic solvent (chloroform) by a solution blending method to prepare a coating solution with a concentration of 10%-15%.
[0143] Coating process: The waterproof coating is evenly coated on the surface of the substrate layer by roller coating, and the coating thickness is controlled between 0.3μm and 0.5μm.
[0144] Heat treatment: Place the coated film in an oven and heat treat it at 170°C for 15-20 minutes to ensure that the coating is firmly bonded to the substrate layer and obtain excellent waterproof performance.
[0145] Preparation of breathable membrane layer
[0146] Material selection: The breathable membrane layer is made of a composite material of polyester fiber and polyurethane (PU), with a polyester content of 60% and a polyurethane content of 40%.
[0147] Solution preparation: dissolve the polyurethane and polyester fiber in an organic solvent and adjust the solution concentration to 15%-20%.
[0148] Coating process: The breathable film is coated on the aforementioned substrate layer using a knife scraping method, and the coating thickness is controlled at 1 μm to 1.5 μm.
[0149] Air permeability control: By adjusting the solution concentration and coating process, the porosity of the film layer reaches 15%-20%, and the breathable film layer is ensured to have a high water vapor transmission rate (MVTR) value of 8000-12000g / m 2 ·24h.
[0150] Curing treatment: Use hot air drying to dry the film at 120°C for 30 minutes to make the surface of the breathable film layer smooth and maintain good air permeability.
[0151] Preparation of antifouling and antibacterial coating
[0152] Material selection: The antifouling and antibacterial coating uses a composite material of nano-silver particles and siloxane, with a nano-silver content of 5%-8%.
[0153] Solution preparation: Disperse the nanosilver particles in an alcohol solvent, add an appropriate amount of siloxane (such as organosilicon silicon dioxide powder), and prepare a coating solution with a concentration of 3%-5%.
[0154] Coating process: The antifouling and antibacterial solution is evenly sprayed on the surface of the membrane by spraying, and the coating thickness is controlled between 0.1μm and 0.3μm.
[0155] Curing treatment: The coating film is placed in a UV curing device and the coating is cured using a UV light source to ensure that the activity of the nanosilver particles remains unchanged and provide lasting antibacterial properties.
[0156] Synthesis and hot pressing of integrated layers
[0157] Interlayer bonding: hot pressing is performed between the waterproof coating layer, the breathable membrane layer and the substrate layer so that the layers can be fully bonded to form a composite film with triple functions (waterproof, breathable, antifouling and antibacterial).
[0158] Hot pressing process: Use a hot press machine for hot pressing treatment, the pressing temperature is set to 150°C, the pressure is 12-18MPa, and the time is controlled to 15-20 minutes to ensure the bonding force between the layers and the overall strength of the film layer.
[0159] Cooling process: Natural cooling to room temperature to ensure that the film structure is stable and the layers are firmly bonded.
[0160] Final product performance testing
[0161] Waterproof performance: The waterproof performance of the membrane is tested by international standard test methods (such as ISO 811 or AATCC 127) to ensure that the water column height is not less than 10000mm, achieving excellent waterproof effect.
[0162] Breathability: Through the water vapor transmission rate (MVTR) test, ensure that the water vapor transmission rate of the film is 8000-12000g / m 2 24 hours, suitable for protection needs in high-intensity activities or hot and humid environments.
[0163] Durability test: Through wear resistance, washing resistance and UV aging resistance tests, it is ensured that the waterproof and breathable performance of the film is not significantly affected after long-term use, and it meets the needs of multiple washing and long-term exposure.
[0164] Antibacterial performance: The antibacterial activity of the membrane surface is tested using the ISO 22196 standard to ensure that the antibacterial rate reaches more than 99% within 24 hours, effectively inhibiting the growth of common bacteria.
[0165] Optical performance: Test the light transmittance of the film to ensure that the film does not affect the normal visual effect during use, and the light transmittance is controlled between 80% and 90%.
[0166] Of course, the above are only typical examples of the present invention. In addition to these, the present invention may also have many other specific implementations. Any technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection required by the present invention. Of course, the above are only typical examples of the present invention. In addition to these, the present invention may also have many other specific implementations. Any technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection required by the present invention.
Claims
1. A multi-layer co-extruded optical film, characterized in that , the film is composed of the following components: a polymer substrate layer, the layer consisting of polyester and polymethyl methacrylate; UV blocking film, which is composed of titanium dioxide and zinc dioxide; Multilayer reflective film, which is formed by alternating stacking of high refractive index materials and low refractive index materials; Heat reflective film, which is composed of metallic reflective material; a superhydrophobic coating composed of a fluorinated polymer; Anti-scratch protective layer, the protective layer consists of polyurethane material.
2. The multilayer co-extruded optical film according to claim 1, characterized in that: The polymer substrate layer consists of a mixture of polyethylene terephthalate and polymethyl methacrylate.
3. The multilayer co-extruded optical film according to claim 1, characterized in that: The ultraviolet blocking film is formed by a sol-gel method, and the titanium dioxide and zinc dioxide are dispersed in a transparent substrate in the form of nanoparticles.
4. The multilayer co-extruded optical film according to claim 1, characterized in that: The multilayer reflective film is composed of at least 10 layers of high refractive index materials and low refractive index materials stacked alternately.
5. The multi-layer co-extruded optical film according to claim 1, characterized in that: The super hydrophobic coating is made of fluorinated ethylene or fluorinated polyurethane material.
6. The multi-layer co-extruded optical film according to claim 1, characterized in that: The anti-scratch protective layer is a polyurethane coating with a hardness greater than 4H and a coating thickness of 0.5-2.0 μm.
7. The multi-layer co-extruded optical film according to claim 1, characterized in that: The thickness ratio of the polymer substrate layer, the ultraviolet blocking film and the multilayer reflective film is 1:1:
2.
8. The multi-layer co-extruded optical film according to claim 1, characterized in that: The high refractive index material is one of titanium dioxide, silicon dioxide and zinc sulfide, the low refractive index material is one of silicon dioxide and magnesium fluoride, and the metal reflective material is one of aluminum, silver or nickel.
9. The multilayer co-extruded optical film according to any one of claims 1 to 8, characterized in that: The film is co-extruded, and all layer materials are co-extruded simultaneously through multiple extruders in a molten state. The total thickness of the film is between 10 μm and 100 μm.
10. A method for preparing a multi-layer co-extruded optical film, characterized in that , including the following steps: The polyester and polymethyl methacrylate are mixed in a certain proportion, an appropriate amount of additives are added, and then a uniform polymer substrate layer is formed by melt co-extrusion technology; The titanium dioxide and zinc dioxide powders are dispersed in a suitable solvent, the titanium dioxide and zinc dioxide are mixed by a sol-gel method, and then coated on the surface of the polymer substrate layer, and then heat-treated to remove the solvent to form a UV blocking film; Using alternating evaporation deposition technology, high refractive index material and low refractive index material are deposited layer by layer on the UV blocking film. The thickness of each layer of material is usually 20-30nm to form the required multi-layer reflective film. Using physical vapor deposition method, metal reflective material is evaporated on the top layer of multi-layer reflective film; The fluorinated polymer is coated on the heat reflective film, and the fluorinated polymer is evenly coated on the surface of the film by a solution coating method, and then dried after coating; Applying polyurethane material as an anti-scratch protective layer, the protective layer is applied by solution coating, and heat curing is performed after the coating is completed; After the above steps are completed, all layers of the film are subjected to an overall heat pressing treatment at a temperature of 100-150°C for 15-30 minutes.
Citation Information
Patent Citations
Transparent laminated film and method for producing the same
CN102224004A
Multi-layer optical coating structure having an antibacterial coating layer
CN104339749A
Film having hard coat layer, antireflection films and their manufacturing methods
JP2002107501A
Laminate
JP2019136954A
Optical laminate, display unit, display, production method of optical laminate
JP2024093111A